2009
DOI: 10.4103/0019-5545.58290
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in South India: A community-based study in Kerala

Abstract: Background:Studies from Tamil Nadu, South India, have reported the world's highest suicide rates. As per official reports, Kerala, another South Indian state has the highest suicide rate among the major states in India.Objective:The purpose of this analysis is to estimate the rates and age-specific incidence of suicide in a rural community in Kerala, under continuous observation for the last five years.Settings and Design:The study setting comprised of seven contiguous panchayats constituting a development blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 14 publications
2
41
2
Order By: Relevance
“…This is similar to study conducted in Kerala, Tamil Nadu and also supported by nationally representative survey published in Lancet. 2,11,12 Level of education, occupation, marital status, religion, caste or type of family was not associated with suicidal ideation or attempt in the present study. This is contrary to findings by Narang et al who reported that single men and married women were more at risk of committing suicide.…”
Section: Discussioncontrasting
confidence: 64%
“…This is similar to study conducted in Kerala, Tamil Nadu and also supported by nationally representative survey published in Lancet. 2,11,12 Level of education, occupation, marital status, religion, caste or type of family was not associated with suicidal ideation or attempt in the present study. This is contrary to findings by Narang et al who reported that single men and married women were more at risk of committing suicide.…”
Section: Discussioncontrasting
confidence: 64%
“…The suicide rates in Kerala are the highest in the country at 27.7 per 100,000 compared with 0.6 per 100,000 in Bihar (Soman et al 2009). …”
Section: Impact Of Using Private Healthcare On Che (Stratified By Prementioning
confidence: 95%
“…[20] Some studies have estimated the annual suicide rate based on data from smaller samples and using different methods, such as hospital-based samples, longitudinal cohort,[26] emergency service[27] and verbal autopsy[2832] [Table 1]. Studies using verbal autopsies report that suicide rates are 2-3 times higher than those reported in other studies.…”
Section: Epidemiologymentioning
confidence: 99%